Risk evaluation of ballistic penetration by small caliber ammunition of live-fire shoot house facilities with comparison to numerical and experimental results. Issue 4 (December 2021) - Davis, Brad Gregory; Thompson, Jacob; Morningstar, William; McCool, Ean; Peri, Vishnu; Davidson, F. Todd
The development of advanced small caliber weapon systems has resulted in rounds with more material penetration capabilities. The increased capabilities may mean that existing live-fire facilities will no longer be adequate for the training and certification of military and law enforcement personnel. Constraints on training in many live-fire shoot house facilities are already in place, with some allowing only single round impact during training. With little understanding of the probability of perforation, or failure, of existing containment systems, this study evaluates risk by studying the single round impact of small caliber ammunition against live-fire shoot house containment systems constructed from AR500 steel panels with two-inch ballistic rubber covering. An analytical and numerical study was conducted using an existing model for steel penetration developed by Alekseevskii-Tate and the EPIC finite element code. A modified form of the advancing cavity model for the ballistic resistance of the target material was used to account for the relatively unconfined material resulting from the studied impacts. These results are then compared to experimental tests conducted by Goodman for rounds of various small calibers impacting live-fire facility containment systems. Projectile and target characteristics were then modeled as continuous random variables, and Monte Carlo simulations were conducted using the validated analytical model to estimate the probability of a single round impact perforating the live-fire facility containment system. An importance sampling scheme was used to reduce the variance of the solution and provide a more accurate estimate of the probability of failure. The Alekseevskii-Tate model was found to provide accurate estimates of the depth of penetration when compared to experimental and numerical results at ordnance velocities and an estimate of the probability of failure is on the order of 1x10 -5 . This study provides useful tools for the analysis of existing live-fire facilities against future and existing ammunition, and for the design of new facilities. When coupled with Monte Carlo simulation techniques, a risk-based approach to certify live-fire facilities for use with any variety of small arms ammunition can be applied.